1996
DOI: 10.1152/ajplung.1996.271.5.l734
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke-induced lung emphysema in guinea pigs is associated with increased interstitial collagenase

Abstract: We examined the expression of interstitial collagenase and its enzymatic activity in lung damage induced by tobacco smoke. Guinea pigs were exposed to the smoke of 20 cigarettes per day from 1-8 wk. Age-matched guinea pigs were used as controls. At 6 and 8 wk of smoke exposure, lungs exhibited interstitial and peribronchiolar inflammation and moderate emphysematous changes. In situ hybridization of injured lungs revealed patchy expression of collagenase mRNA mainly in macrophages but also in alveolar epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 0 publications
5
41
0
1
Order By: Relevance
“…The present study links this same kinase pathway to increased MMP-1 expression seen in emphysema and alveolar destruction (10). The MAP kinase pathway is also implicated in apoptosis (37-39), a cell death mechanism associated with emphysema (14,40,41). Together, these studies suggest a central role for ERK in cigarette smoke-induced MMP-1 activity in lung epithelia and in multiple emphysema-associated pathologies.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The present study links this same kinase pathway to increased MMP-1 expression seen in emphysema and alveolar destruction (10). The MAP kinase pathway is also implicated in apoptosis (37-39), a cell death mechanism associated with emphysema (14,40,41). Together, these studies suggest a central role for ERK in cigarette smoke-induced MMP-1 activity in lung epithelia and in multiple emphysema-associated pathologies.…”
Section: Discussionsupporting
confidence: 61%
“…Evidence from human tissue and animal models support a role for collagenolytic enzymes in emphysema pathogenesis (9,10,13). Elevated MMP-1 levels and decreased pulmonary collagen content are measured in guinea pigs after cigarette smoke exposure (12,14). Transgenic mice expressing human collagenase (MMP-1) develop emphysematous changes in their lungs (10) caused by months of proteolytic damage to the lung parenchyma (15).…”
mentioning
confidence: 99%
“…In guinea pigs, exposure to cigarette smoke produces emphysematous changes that are associated with increased levels of collagenase messenger RNA, resulting in collagen loss. 34 In mice exposed to cigarette smoke, the lack of MMP-12 activity prevents emphysema development and macrophage infiltration. 9,10 In humans, an analysis of protease production by alveolar macrophages in vitro has shown an increased expression of MMP-9 and MMP-12 in subjects with emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Increased whole lung MMP-1 mRNA and protein has been demonstrated in human and guinea pig emphysema [48,76,77], with increased immunoreactivity found in macrophages and in airway epithelium. GOSSELINK et al [51] reported that MMP-1 gene expression increases in the parenchyma from GOLD stage 0 to 3/4, although the magnitude of the difference overall was fairly small.…”
Section: Emphysema: Role Of Other Mmpsmentioning
confidence: 99%